Sexual function in adult patients who have undergone augmentation surgery in childhood: what is really important? - Bañuelos Marco, Beatriz; Hiess, Manuela; Stein, Raimund; Gonzalez, Ricardo; Lingnau, Anja; Wood, Dan; Radford, Anna; Haid, Bernhard (International journal of impotence research, 2021)
Problems relating to the development of a healthy approach to sex and intimacy during puberty, after augmentation cystoplasty, are scarcely discussed in literature. Therefore, this may suggest that such issues are insufficiently addressed by pediatric urologists. We gathered four experts in the field as well as an experienced leader of a patient group and mother of a girl with spina bifida and asked questions relevant to the following areas of care: (a) diversion, urinary incontinence, and sexual life; (b) impact of a stoma on body image perception and self-esteem; (c) specific female concerns with regard to fertility and recurrent urinary infections; (d) specific male concerns on anejaculation and erectile dysfunction. Their answers are discussed in view of the available literature. All experts and the patient group representative agreed that most of these patients will experience: lack of self-confidence as the most frequent obstacle to starting a relationship and incontinence as a barrier to sexual activity. The cosmesis of the stoma and abdominal scars might influence self-esteem and therefore the sexual activity, however it appears to be a less common concern in males than females. Our results outline the importance and influence that the body image, self-esteem, and confidence present for the individual expectations of the patients related to sex life and sexual activity. Physicians should be encouraged to ask all postpubertal patients about their sexual concerns at every visit. Further studies and exchange of information between clinicians are needed to provide meaningful and analyzable patient-related outcome measures (PROMs).